KOLABORASI PENERAPAN MODEL PEMBELAJARAN ROUND TABLE DAN BROWN TERHADAP PENINGKATAN KEMAMPUAN MENULIS CERPEN SISWA KELAS IX IBNUSINA SMPN MODEL TERPADU MADANI PALU - Ervina, Ervina; Suputra, I Gusti Ketut Alit; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
The ability of writing short story of the eleventh-graders Ibnusina SMP Negeri Model Terpadu Madani Palu can be improved. Problem of this research are: 1) how is the implementation of collaborative steps of round table and brown learning model in improving writing short story ability the eleventh-graders Ibnusina SMP Negeri Model Terpadu Madani Palu? and 2) can the ability of writing short story improved after the collaboration of round table and brown learning model? This research intends to: 1) describe stages of the application of round table and brown learning model in improving writing short story ability the eleventh-graders Ibnusina SMP Negeri Model Terpadu Madani Palu, 2) describe the result of writing short story ability after the application of round table and brown learning model. Data were collected through written test and non test (observation and documentation). Data were analyzed qualitatively and quantitatively. The result of this research revealed that: 1) the application of round table and brown learning model through several stages, first the researcher plays video of short story watched by students; second, researcher prepares observation sheet of the implementation of writing short story; third, researcher prepares camera for documentation of teachers’ and students’ activities in the learning process. Students’ ability in writing short story improves after conducted stages above. The percentage of improvement is increase in every meeting of Cycle I and Cycle II. Cycle I show 80.18 from 73.51 and improved to 83.88 in Cycle II. Round Table Learning Model and Brown